Neurokinin A is the predominant tachykinin in human bronchoalveolar lavage fluid in normal and asthmatic subjects. Issue 5 (1st May 1998) - Heaney, L G; Cross, L J M; McGarvey, L P A; Buchanan, K D; Ennis, M; Shaw, C
Abstract : BACKGROUND: Multiple sensory neuropeptides are present in human airways and may contribute to diseases such as asthma. This study quantified and characterised substance P (SP), neurokinin A (NKA), and calcitonin gene related peptide (CGRP) immunoreactivity in bronchoalveolar lavage fluid in asthmatic and normal subjects. METHODS: Using specific radioimmunoassay (RIA), SP, NKA and CGRP were measured in bronchoalveolar lavage fluid from asthmatic subjects (n = 5), normal subjects (n = 5), atopic non-asthmatic subjects (n = 6), and asthmatic subjects four hours after allergen challenge (n = 12). Peptide immunoreactivity was characterised using high performance liquid chromatography (HPLC) and RIA. RESULTS: No SP or CGRP immunoreactivity was detected in any of the fractions from samples after extraction, HPLC, and RIA. Non-specific binding resulted in spurious SP immunoreactivity being detected in bronchoalveolar lavage fluid when no extraction process was employed. NKA was detected in significant amounts in asthmatic (median 550, range 425–625 pg/ml) and normal subjects (median 725, range 350–1425 pg/ml). The level of NKA was significantly higher in the asthmatic subjects after allergen challenge (median 750, range 350–1250 pg/ml) than in unchallenged asthmatic subjects (median 600, range 425–600 pg/ml, p<0.01). CONCLUSIONS: Extraction and characterisation of peptides from bronchoalveolar lavage fluid must be performed to ensure that the measured immunoreactivity represents target peptide. NKA is present in bronchoalveolar lavage fluid in high concentrations and is the predominant tachykinin. The concentrations of NKA are similar in normal subjects and subjects with mild asthma.